1600 Treatment of essential tremor: report on 200 patients. Issue 3 (9th February 2012) - Bain, P; Nigmatullina, Y
Abstract : 200 consecutive patients with essential tremor (ET) were examined to study the effectiveness of anti-tremor treatments. Tremor affected the arms in 98% of patients, head in 35%, legs in 14% and jaw in 11%. Intention tremor and rest tremor were seen in the arms of 76% and 27% of patients respectively. Intention tremor was associated with longer disease duration. 19% had gait abnormalities. 24% and 11% of ET patients suffered from depressive and anxiety symptoms respectively. Alcohol reduced the tremor amplitude in 66% of patients. All the routinely deployed anti-tremor drugs reduced tremor in <40% of patients except for propranolol which did so in 43%. 73% of patients reported adverse effects from primidone and 52% from propranolol. More than 50% of patients had to stop their antitremor medication as a result of intolerable side effects or lack of benefit from treatment. We derived a quality of treatment index (QTI=% responding/% withdrawing from a drug) for the anti-tremor drugs in order to estimate their usefulness as therapies for ET. No antitremor drug had a QTI>1. An inverse association was seen between tremor severity and tremor responsiveness to medication. 10 patients underwent stereotactic surgery with considerable improvement and minimal side-effects. Conclusion: Pharmacotherapy provides limited benefit in ET, with frequent treatment related adverse effects. Surgery should be considered earlier for patients with severe ET as medication is ineffective.